Decoding digital philanthropy analyzing donors choices in cryptocurrency donations - Keshvari Fard, Milad; Liu, Jingshu; Petropoulos, Fotios (SSRN: Social Science Research Network, 2024)
Since Bitcoin’s inception in 2009, cryptocurrencies have found applications in various domains. However, despite the unique potential of cryptocurrencies for the nonprofit sector, especially in fundraising, there is a scarcity of research on the behavior of crypto donors. In this research, we investigate key attributes of cryptocurrencies that correlate with the amount of donations made in that specific digital currency, and explore characteristics of digital wallets that predict the donation behavior of wallet holders. For our regression analysis, we use donation data from the Aid for Ukraine campaign, one of the largest cryptocurrency fundraising initiatives launched in response to the Russian invasion of Ukraine. Our findings indicate that cryptocurrencies with a larger market cap and higher age tend to be favored by donors, while those associated with higher transaction fees are preferred less frequently. Donors also exhibit a propensity to contribute more in cryptocurrencies of higher price volatility. Moreover, everything else equal, stablecoins are used more often for donations. On the other hand, our results highlight that frequent cryptocurrency users tend to make larger crypto donations and are more inclined to continue supporting the campaign through future contributions. Furthermore, donors with identifiable names for their wallets tend to donate larger amounts, although this feature does not predict their inclination for future contributions.
SSRN - pre-print
Keywords: Cryptocurrency; Philanthropy; Donation; Blockchain; Crowdsourcing; Aid For Ukraine